Converting Food Waste Generation from Household Using Bokashi Method for Composting - Awang, Hasslina; Awang, Zarizi (Progress in Engineering Application and Technology, 2021)
In Malaysia, around 8000 tonnes of food and kitchen waste is produced every day and is sent to landfill that produces methane gas, bad odor and greenhouse effect. Also, impacts on social and economic. Thus, the objectives of the study are to design a suitable Bokashi bin in achieving an affordable and practical usage for the household, to convert the food waste generated from the household into an organic soil fertilizer via the best formulated Bokashi method using effective microorganism (EM). Next, to analyse the effect of Bokashi application on plant growth as an organic soil fertilizer. A Bokashi bin is designed with low cost and less maintenance to handle, three different quantity of EM were used for the formulation of EM Bokashi for 7 days, fermented in an airtight container for 14 days, buried the fermented food waste for 30 days and applied of Bokashi on plant growth (Carica papaya L.) for 35 days. Parameters with the height of the plant, number of leaves, number of the branch and length of leaves are analysed used different ratios and treatment. The result showed T4 (1 kg of soil and 600 gm of Bokashi compost) gave the highest performance mean with 16.96 cm (height of plant), 6.40 (number of the branch), 3.60 cm (length of leaves) and 6.40 (number of leaves) than T1, T2 and T3. This study helps to minimize environmental pollution, eliminate bad odor caused by food waste and a sustainable method in achieving zero waste in the future.